Pharmacological characterization of lipidized analogs of prolactin-releasing peptide with a modified C- terminal aromatic ring - Prazienkova, V; Ticha, A; Blechova, M; Spolcova, A; Zelezna, B; Maletinska, L (Journal of physiology and pharmacology, 2016)
Prolactin-releasing peptide (PrRP) is an anorexigenic neuropeptide expressed in the brain where it regulates food intake and energy expenditure. The C-terminal Arg-Phe-NH2 of PrRP is crucial for its biological activity. In our previous study, we showed that PrRP analogs myristoylated or palmitoylated at the N- terminus seem to cross the blood-brain barrier and lower food intake following peripheral administration. In this study, myristoylated and palmitoylated PrRP31 analogs with a modified C-terminal Phe were designed and tested. Lipidized analogs containing Phe(31) replaced by aromatic non-coded amino acids or tyrosine revealed high binding affinity to rat pituitary RC-4B/C cells with endogenous PrRP and neuropeptide FF 2 receptors and to CHO-K1 cells overexpressing either PrRP or neuropeptide FF 2 receptors. The analogs also showed strong agonistic properties at the GPR10 receptor using the beta-lactamase reporter gene assay. Moreover, lipidized PrRP analogs, especially those that were palmitoylated, demonstrated strong and long-lasting anorexigenic effects in fasted mice after subcutaneous administration. The most efficient PrRP31 analogs with PheCl2(31), either palmitoylated or myristoylated at the N-terminus, are promising candidates for the study of food disorders, possibly for anti-obesity treatment. Despite the therapeutic potential in targeting central GPR10, the endogenous ligand PrRP cannot cross the blood-brain barrier. Understanding biological activity and transport of novel structural analogs of PrRP with a potential central anorexigenic effect is of key therapeutic significance.
Keywords: Blood-Brain Barrier; receptory neuropeptidů; Cell Line; Male; Obesity; přijímání potravy; Brain; neuropeptidy; Receptors, Neuropeptide; CHO Cells; obezita; mužské pohlaví; Eating; Prolactin-Releasing Hormone; Cricetulus; krysa rodu Rattus; lipidy; Animals; lidé; CHO buňky; Humans; zvířata; Rats; myši inbrední C57BL; mozek; myši; buněčné linie; hormon uvolňující prolaktin; Mice, Inbred C57BL; Lipids; Mice; Neuropeptides; hematoencefalická bariéra